Parkinsonian-Pyramidal syndromes: A systematic review. (June 2017) - Tranchant, Christine; Koob, Meriam; Anheim, Mathieu
Abstract: Introduction: Parkinsonian-Pyramidal syndrome (PPS), defined as the combination of both pyramidal and parkinsonian signs is a concept that recently emerged. PPS may manifest itself in numerous neurodegenerative diseases, many of these being inherited. Their diagnosis is a major challenge for the clinical management, for the prognosis, for genetic counselling and, in a few cases, which should not be neglected, for specific treatment. Objective: Our objective is to provide a review of PPS and an algorithm in order to guide their diagnosis in clinical practice. Methods: We performed an exhaustive PubMed and OMIM research matching the following key words: "Parkinsonism and pyramidal signs" or "Parkinsonism and spasticity" or "pallido-pyramidal syndrome" or "Parkinsonism and spastic paraplegia". English publications from the last ten years were included. Results: We propose a pragmatic presentation based on several established classifications and we will distinguish inherited PPS found in complex hereditary spastic paraplegia, young onset parkinsonism, neurodegeneration with brain iron accumulation, primary familial brain calcifications, inborn errors of metabolism, and few rare others inherited neurodegenerative diseases, then non-inherited neurodegenerative PPS. We therefore suggest guidelines (based on age at onset, family history, associated clinical signs, brain MRI findings as well as certain laboratory investigations), for the diagnosis and the management of PPS. Many pathophysiological pathways may underlie PPS but the most frequent are those usually involved in both inherited Parkinson's disease and spastic paraplegia, i.e. mitochondrial pathway, vesicular trafficking including endosomal and lysosomal pathways as well as autophagy. Highlights: Parkinsonian-Pyramidal syndrome (PPS), defined as the combination of both pyramidal and parkinsonian signs, is a concept that recently emerged. Their diagnosis is a major challenge for the clinical management, for the prognosis, for genetic counselling and, in a few cases, which should not be neglected, for specific treatment. We provide a systematic review of PPS and suggest guidelines for diagnosis and the management of PPS in clinical practice, based on age at onset, family history, associated clinical signs (ocular and oculomotor signs, movement disorders, mental retardation/cognitive decline, peripheral neuropathy), brain MRI findings as well as certain laboratory investigations.